Trends and hotspots on the relationship between gut microbiota and Parkinson’s Disease: a bibliometric analysis - Li, Xuefeng; Hao, Xiaogang; Chen, Chunhai; Zhai, Chao; Pan, Ting; Zhou, Xue; Liu, Yang (Frontiers in Cellular and Infection Microbiology, 2024)
Parkinson’s disease (PD) is a neurodegenerative disorder that significantly impacts patients’ quality of life. Recent evidence has highlighted a complex relationship between the gut microbiota (GM) and PD. Understanding this relationship is crucial for potentially targeting GM in PD treatment and expanding therapeutic options. This study aimed to comprehensively analyze the global landscape, trends, and research focus on GM and PD using bibliometric analysis. Utilizing publications from the Web of Science Core Collection (WsSCC), bibliometric tools such as the R package ‘Bibliometrix,’ VOS viewer, and CiteSpace software were employed to assess parameters like yearly publications, countries/regions, institutions, and authors. Research trends and hotspots were identified through keyword analysis. The results revealed 1,161 articles published between 2013-2023, with China leading in publications (n=352, 30.31% of total), while the United States had a higher influence (H-index=58). The University of California System was the top institution in terms of publications (n=35), with the National Natural Science Foundation of China funding the most projects (n=172). Keshavarzian A and Sampson TR were the authors with the highest publication and co-citation counts, respectively. The International Journal of Molecular Sciences had the most articles published (n=48). Keyword analysis identified parkinson’s disease, gut microbiota, short-chain fatty acids, inflammation, and probiotics as main research topics. Biomarkers, ketogenic diet, and NF-κB were recent research hotspots and trends (2021-2023). The current study conducts an objective and comprehensive analysis of these publications, identifying trends and hotspots in the field of research. The findings offer valuable insights to scholars globally and in-vestigate potential therapeutic strategies for Parkinson’s Disease.